Evaluation of Knowledge Levels and Comparative Quality of Life (OHIP-14) Between Denture Wearers and Non-Wearers among the Elderly at Panti Sosial Tresna Werdha Budi Luhur Jambi City - Maqdisa, Siti Risa; Mardhian, Deby Fajar; Febrida, Renny (Jurnal Kesmas Jambi, 2026)
Tooth loss in the elderly significantly impacts their quality of life. Low oral health literacy often acts as a major barrier to prosthetic rehabilitation. This study aimed to analyze the effect of an educational intervention on oral health literacy and to compare oral health-related quality of life between denture wearers and non-wearers among the elderly at Panti Sosial Tresna Werdha (PSTW) Budi Luhur, Jambi. A pre-experimental study with a one-group pretest-posttest design was conducted on 45 elderly participants. Oral health literacy levels were measured before and after an educational intervention and analyzed using the Wilcoxon Signed-Rank Test, while quality of life was evaluated using the Oral Health Impact Profile-14 (OHIP-14) instrument and compared between denture wearers and non-wearers using the Independent Samples t-test/Mann-Whitney U Test. The mean oral health literacy score increased significantly from 3.98 to 6.27 (p=0.000). A significant difference in quality of life was found between denture wearers (score 6.33) and non-wearers (score 39.68) with p=0.000, though this cross-sectional comparison cannot establish a causal relationship. The educational intervention is effective in improving elderly oral health literacy, and denture use is strongly correlated with a better quality of life. Integrated prosthetic rehabilitation programs are highly recommended to enhance the well-being of the elderly.